2008
DOI: 10.1038/ja.2008.124
|View full text |Cite
|
Sign up to set email alerts
|

Essramycin: A First Triazolopyrimidine Antibiotic Isolated from Nature†

Abstract: In the course of our screening program for new bio-active compounds, a novel triazolopyrimidine antibiotic, essramycin (1), was obtained from the culture broth of the marine Streptomyces sp., isolate Merv8102. Structure 1 was established by intensive NMR studies and by mass spectra. The compound is antibacterially active with MIC of 2 to 8 mg/ml against Gram-positive and Gramnegative bacteria, while it showed no antifungal activity. The fermentation and isolation, as well as the structure elucidation and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 12 publications
2
115
0
Order By: Relevance
“…Thus, compound 5 reacted with cyclic α,β-unsaturated ketones type (6-8) in dimethylformamide for 6-7 h afforded compounds (9)(10)(11) in good yield. Whereas, triazolo pyrimido [4,5-b]quinolines 12-14 were achieved when the reaction mixture was refluxed for a longer time of 45 h. In another route compounds 12 were prepared by refluxing of compound 9 in DMF for 15 h (Scheme 2).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, compound 5 reacted with cyclic α,β-unsaturated ketones type (6-8) in dimethylformamide for 6-7 h afforded compounds (9)(10)(11) in good yield. Whereas, triazolo pyrimido [4,5-b]quinolines 12-14 were achieved when the reaction mixture was refluxed for a longer time of 45 h. In another route compounds 12 were prepared by refluxing of compound 9 in DMF for 15 h (Scheme 2).…”
Section: Introductionmentioning
confidence: 95%
“…The diameter of inhibition zone was measured as an indicator for the activity of the compounds. The results for antibacterial activities depicted in Table 1 revealed that compounds 10,11,25,28,31,32,33, and 34 were the most effective against Staphylococcus aureus and Bacillus subtilis and have moderate activity against Pseudomonas aeruginosa, and Escherichia coli. On the other hand, most of the prepared compounds exhibited low to moderate antifungal activities against the reference drugs, whereas compounds 25, 28, 31, 32, 33, and 34 were the most effective against Aspergillus fumigatus and Geotrichum candidum and have moderate activity against Candida albicans, and Syncephalastrum racemosum ( Table 2).…”
Section: Introductionmentioning
confidence: 97%
“…A C-2 substituent affects the ipso C atom of 1,2,4-triazolo[1,5-a]pyrimidines, however, the influence on the 13 C shifts of the other ring atoms is negligible (Table 41) [422] . Essramycin (288) is antibacterially active with minimum inhibitory concentrations (MIC) of 2 to 8 µg/ml against Gram-positive and Gram-negative bacteria, while it showed no antifungal activity [419] .…”
Section: Essramycinmentioning
confidence: 99%
“…After working up and isolation using RP-18 column chromatography, a colourless solid of essramycin (288) was obtained ( Figure 161). Details of the working up, isolation and identification of essramycin (288) were described in a recent article [419] .…”
Section: Marine Streptomyces Sp Isolate Merv8102mentioning
confidence: 99%
See 1 more Smart Citation